Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.4049/jimmunol.166.2.1114
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conserved Regions of the Immunodominant Major Surface Protein 2 of the Genogroup II Ehrlichial Pathogen Anaplasma marginale Are Rich in Naturally Derived CD4+ T Lymphocyte Epitopes that Elicit Strong Recall Responses

Abstract: Genogroup II ehrlichia, including the agent of human granulocytic ehrlichiosis, Ehrlichia phagocytophila, and the bovine pathogen Anaplasma marginale, express a markedly immunodominant outer membrane protein designated major surface protein 2 (MSP2). MSP2 is encoded by a multigene family, resulting in the expression of variant B cell epitopes. MSP2 variants are sequentially expressed in the repeated cycles of rickettsemia that characterize persistent A. marginale infection and control of each rickettsemic cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
81
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 50 publications
(30 reference statements)
2
81
0
4
Order By: Relevance
“…We demonstrated that CD4 T cells from IOE-infected mice proliferated in response to IOE Ags and secreted type I cytokines that were essential for host defense. The conclusion that CD4 T cells play an essential role during IOE infection is supported by data from other studies that have demonstrated a requirement for CD4 T cells during ehrlichial infection (12,14,31,32) as well as other intracellular bacterial infections (1,(33)(34)(35)(36). One likely role of CD4 T cells during IOE infection is to induce, via inflammatory cytokines, production of reactive nitrogen and/or oxygen species that may be responsible for the killing of intracellular ehrlichiae within macrophages (11).…”
Section: Discussionsupporting
confidence: 64%
“…We demonstrated that CD4 T cells from IOE-infected mice proliferated in response to IOE Ags and secreted type I cytokines that were essential for host defense. The conclusion that CD4 T cells play an essential role during IOE infection is supported by data from other studies that have demonstrated a requirement for CD4 T cells during ehrlichial infection (12,14,31,32) as well as other intracellular bacterial infections (1,(33)(34)(35)(36). One likely role of CD4 T cells during IOE infection is to induce, via inflammatory cytokines, production of reactive nitrogen and/or oxygen species that may be responsible for the killing of intracellular ehrlichiae within macrophages (11).…”
Section: Discussionsupporting
confidence: 64%
“…The striking immunodominance of A. marginale MSP2 has been attributed to both protein abundance and the presence of multiple CD4 ϩ T-cell epitopes in the hypervariable region and flanking conserved regions (1,(6)(7)(8). The data presented here provide a third mechanism for immunodominance: processing of MSP2 T-cell epitopes from native MSP2 and MSP3 with presentation to CD4 ϩ T cells.…”
mentioning
confidence: 99%
“…In the N terminus of MSP2, amino acids (aa) 46 to 69 are 70.8% identical to those of positions 51 to 74 in MSP3, and aa 116 to 144 in MSP2 are 82.7% identical to those in positions 128 to 156 of MSP3 (14). Previous studies had determined that aa 101 to 142 of MSP2 contained at least two Th-cell epitopes recognized by MSP2 vaccinees (animals 59 and 61 [7]), enabling us to test whether CD4 ϩ T cells from these cattle would respond to the corresponding sequence in MSP3. To this end, peptides P6 and P7, previously shown to stimulate CD4 ϩ T-cell lines from MSP2-immunized animals 61 and 59, respectively (7), and peptides representing the homologous sequence in MSP3 (Table 1) were tested with short-term T-cell lines from…”
mentioning
confidence: 99%
See 2 more Smart Citations